The judicial House of Lords 1870-2009 - Blom-Cooper, Louis Jacques; Drewry, Gavin; Dickson, Brice (Oxford : Oxford University Press, 2009)
In 2009 a new UK Supreme Court takes on the judicial functions of the House of Lords. In this book a group of over 40 eminent lawyers and legal historians look back over the 130 years of the judicial House of Lords to give a comprehensive history of its role, reputation and impact on the law in the UK and beyond.
Description based on print version record.
Keywords: Great Britain. -- Parliament. -- House of Lords -- History